A comprehensive study of fingertip injuries at a tertiary care centre- fingertip injury outcome score subset pilot - M., Soujanya; Rajput, Darshansingh (International Journal of Research in Orthopaedics, 2024)
Background: Fingertip injury outcome score (FIOS) is a specialized tool designed to assess functional and aesthetic outcomes after treatment of fingertip injuries. It helps both clinicians and researchers evaluate the effectiveness of treatment strategies and monitor patient recovery. This pilot study aims to evaluate the feasibility and effectiveness of a customized FIOS tool using retrospective fingertip injuries data from the hospital, before broader implementation Methods: A retrospective analysis of 58 hand injury patient’s data admitted in hospital with fingertip injuries having tissue loss, between January 2023 and February 2024. A customized FIOS tool, focusing on specific aspects such as complications, aesthetic outcome, patient satisfaction, ability to perform daily tasks and pain, was applied to the collected data. Data analyzed to evaluate how well the FIOS outcome score reflected patient outcomes and clinical findings. Results: The customized FIOS effectively captured key aspects of fingertip injury outcomes, including pain levels, functional recovery. 7% had poor outcome score and 80% of those with poor outcomes suffered injuries from the heavy instruments with complications like revision surgery. 22% of the patients had excellent outcome scores, 53.4% had good aesthetic outcome score. Conclusion: This pilot study demonstrates that using a customized FIOS tool with retrospective data is a viable approach for evaluating fingertip injury outcomes. The findings suggest that the FIOS subset can provide valuable insights into functional and aesthetic recovery. This approach facilitates seamless data capture, minimize duplicated efforts, and reduce errors and discrepancies.